2019
DOI: 10.1002/prep.201800269
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Compatibility of Nitrocellulose with Aniline‐Based Compounds

Abstract: In this paper, the compatibility of nitrocellulose (NC) with some aniline‐based stabilizers was studied in order to detect any interaction between these materials. Both thermal techniques [differential scanning calorimetry (DSC) and vacuum stability test (VST)], and supplementary non‐thermal techniques [Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD) and densimetry] were used. The thermal and non‐thermal measurements showed that NC was highly compatible with N‐(2‐methoxyethyl)‐p‐nitroan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 37 publications
8
36
0
Order By: Relevance
“…According to these results, it can be concluded that the NC2 and MCCN1 synthesized from cellulose and microcrystalline cellulose isolated from marine POBA, respectively, were of high purity, comparable to NC1 prepared from cotton cellulose and MCCN2 produced from C‐MCC. Besides that, it is worthy to note that the FTIR spectra of the produced cellulose nitrate and MCCN are comparable with those reported in the literature …”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…According to these results, it can be concluded that the NC2 and MCCN1 synthesized from cellulose and microcrystalline cellulose isolated from marine POBA, respectively, were of high purity, comparable to NC1 prepared from cotton cellulose and MCCN2 produced from C‐MCC. Besides that, it is worthy to note that the FTIR spectra of the produced cellulose nitrate and MCCN are comparable with those reported in the literature …”
Section: Resultssupporting
confidence: 85%
“…Moreover, the absorption band at 1430–1380 cm −1 is assigned to the asymmetric and symmetric bending vibration of CH 2 group . Additionally, the bands appeared at 1080, 830, 765, and 685 cm −1 , are related to the stretching vibration of CO group, the nitrate ester (ONO 2 ) stretching vibration, and the asymmetric and symmetric deformations of the ONO 2 group . These absorption bands are associated with the typical characteristics of nitrocellulose molecule already reported .…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations